2021
DOI: 10.20452/pamw.15894
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Google Trends in anticipating Coronavirus Disease 2019 (COVID-19) outbreaks in Poland

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
8
1
Order By: Relevance
“…Finally, the pathognomonic COVID-19 symptoms of "smell loss" and "taste loss" displayed relative stability and no significant trend to suggest a positive correlation of these symptoms with the Lambda variant. This is in contrast to previous results published by our team, in which we have shown strong association between SARS-CoV-2 incidence and anosmia or dysgeusia 7,8 Since being first identified in Peru in late 2020, this new SARS-CoV-2 lambda variant has now spread to countries across South America, with cases now being detected all around the world. 12 Among the many mutations associated with the lambda variant, a novel spike protein mutation (L452Q) within the receptor binding domain may offer greater capability to bind to the virus human host receptor (Angiotensin Converting Enzyme 2 (ACE2)) and escape neutralizing antibodies produced from naïve infection, vaccination, or therapeutic antibody cocktails.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Finally, the pathognomonic COVID-19 symptoms of "smell loss" and "taste loss" displayed relative stability and no significant trend to suggest a positive correlation of these symptoms with the Lambda variant. This is in contrast to previous results published by our team, in which we have shown strong association between SARS-CoV-2 incidence and anosmia or dysgeusia 7,8 Since being first identified in Peru in late 2020, this new SARS-CoV-2 lambda variant has now spread to countries across South America, with cases now being detected all around the world. 12 Among the many mutations associated with the lambda variant, a novel spike protein mutation (L452Q) within the receptor binding domain may offer greater capability to bind to the virus human host receptor (Angiotensin Converting Enzyme 2 (ACE2)) and escape neutralizing antibodies produced from naïve infection, vaccination, or therapeutic antibody cocktails.…”
Section: Discussioncontrasting
confidence: 99%
“…Multiple previous studies, either by our group or by other teams which have investigated the trends in online search patterns within the context of regional COVID-19 outbreaks, have consistently shown that the frequency of Google searches of pathognomonic and non-pathognomonic (i.e., general) symptom keywords and SARS-CoV-2 surveillance data have a strong relationship, through which their temporal association enables predicting future trajectories of epidemic based on internet search volumes in a period of time, as well as the demand for SARS-CoV-2 testing and test positivity. [7][8][9] However, this depends on consistency of symptoms over time and may also be influenced by emergence of novel SARS-CoV-2 variants with distinctive biological and clinical characteristics (i.e., higher virulence and/or pathogenicity, immune evasion, greater stability, and so forth).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 In a recent report, Fantini et al have proposed an interesting health approach for anticipating COVID-19 outbreaks, based on an index of transmissibility (T-index), calculated from parameters of coronavirus binding to host cells. 2 Although this strategy seems indeed promising, previous evidence has been garnered that easier and more accessible tools such infodemiology, which relies on investigating the volume of Web searches for specific COVID-19 symptoms, may be effective in anticipating local COVID-19 epidemiological trends, 3 , 4 provided that symptoms caused by the emerging VOCs remain constant over time.…”
Section: Dear Editormentioning
confidence: 99%
“…Highlighted by Gunther Eysenbach, one of the four pillars to fight an infodemic is information monitoring (infoveillance) [6]. Ergo, numerous COVID-19-related infodemiological studies have been conducted worldwide to unravel the information-seeking behavior of the public [7][8][9][10][11][12][13][14][15][16]. In Malaysia, Google is the main search engine with increasing number of Malaysian population utilizing it to search for information on common medical problems [17].…”
Section: Introductionmentioning
confidence: 99%